Analisis Pembentukan Portofolio Optimal Menggunakan Model Indeks Tunggal - Iwan Firdaus; Sri Anah; Fitri Nadira (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2018)
Investors in the capital market will generally invest in stocks that have high returns with minimal risk. In order to reduce the level of risk then the shares can be formed into a portfolio. The purpose of this study was to determine the shares of LQ 45 index members to form the optimal portfolio and to determine the proportion of each stock chosen and the level of return the analysis showed that using Single Index Model approach. Stocks member LQ 45 period every January 2012 to January 2016 ti establish an optimal portfolio is comprised of ASII with a proportion 80,39%, with the proportion of BBCA 0,006% , with the proportion of ICBP 5,07%, with the proportion of UNTR 5,06%, with the proportion of UNVR 9,42% and the rate of profit (expected return) portfolio amounted to 3,65% with a risk of 0,01%.